Training for high school teachers to develop learning modules based on mathematical modeling in Magetan, East Java - Abadi Abadi; Dian Savitri; Rudianto Artiono; Ruli Rahmawati (Community Empowerment, 2024)
Preparing teaching modules that lead to AKM requires skills in framing abstract mathematical material into a situation or problem context known to students. This is a new challenge for teachers. The process of arranging mathematical material into a context familiar to students is called mathematical modeling. However, in practice, teachers often overlook the importance of modeling skills in teaching. This activity aims to equip mathematics teachers with mathematical modeling skills to enhance their teaching, particularly in preparing students for AKM. The activity, attended by 25 MGMP Mathematics High School teachers in Magetan Regency, was conducted in a hybrid manner (offline and online). Based on the analysis of questionnaire data, it can be concluded that there is an improvement in teachers' understanding of the Independent Curriculum, mathematical modeling, and the application of mathematical modeling in preparing teaching modules for mathematics topics. Similarly, there is an increase in awareness of self-development as professional teachers.